Knock-Down of Mucolipin 1 Channel Promotes Tumor Progression and Invasion in Human Glioblastoma Cell Lines - Santoni, Giorgio; Amantini, Consuelo; Nabissi, Massimo; Maggi, Federica; Arcella, Antonietta; Marinelli, Oliviero; Eleuteri, Anna Maria; Santoni, Matteo; Morelli, Maria Beatrice (Frontiers in Oncology, 2021)
Among cancers that affect the central nervous system, glioblastoma is the most common. Given the negative prognostic significance of transient receptor potential mucolipin 1 (TRPML1) channel reduction in patients with glioblastoma, as discussed in previous publications, the aim of the current study was to investigate the biological advantage of TRPML1 loss for glioma cells. Human glioblastoma primary cancer cells (FSL and FCL) and glioblastoma cell lines (T98 and U251) were used for that purpose. TRPML1 silencing in T98 cells induces defective autophagy, nitric oxide (NO) production, and cathepsin B-dependent apoptosis in the first 48 h and then apoptotic-resistant cells proliferate with a high growth rate with respect to control cells. In U251 cells, knock-down of TRPML1 stimulates NO generation and protein oxidation, arrests cell cycle at G2/M phase, and induces autophagy leading to cathepsin B-dependent senescence. Finally, in both cell lines, the long-term effects of TRPML1 silencing promote survival and invasion capacity with respect to control cells. Silencing of TRPML1 also affects the phenotype of glioblastoma primary cells. FSL cells show increased proliferation ability, while FCL cells enter into senescence associated with an increased invasion ability. In conclusion, although the molecular heterogeneity among different glioblastoma cell lines mirrors the intercellular heterogeneity in cancer cells, our data support TRPML1 downregulation as a negative prognostic factor in glioblastoma.